1994
DOI: 10.1089/cap.1994.4.171
|View full text |Cite
|
Sign up to set email alerts
|

Potential Link Between Dietary Intake of Fatty Acids and Behavior: Pilot Exploration of Serum Lipids in Attention-Deficit Hyperactivity Disorder

Abstract: Essential fatty acids are structural components of all biological membranes and form the environment for membrane receptors, ion channels, and enzymes. Dietary linoleic acid is metabolized by delta-6-desaturase to gamma-Iinolenic acid (GLA). Through several further metabolic steps, GLA is eventually converted to series-1 prostaglandins, thromboxanes, and other molecules involved in regulating the moment-to-moment function of various physiological processes. For example, prostaglandins interact with dopamine ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In these studies, fatty acids were administered individually or in combination, as monotherapy or as an add-on to existing pharmacotherapy. Early studies on the effect of the sole administration of the ω-6 fatty acid GLA to hyperactive and ADHD children established merely a minimal therapeutic benefit [3,6,7]. Likewise, the administration of ω-3 fatty acids in monotherapy form was ineffective.…”
Section: Results From Clinical Trialsmentioning
confidence: 99%
“…In these studies, fatty acids were administered individually or in combination, as monotherapy or as an add-on to existing pharmacotherapy. Early studies on the effect of the sole administration of the ω-6 fatty acid GLA to hyperactive and ADHD children established merely a minimal therapeutic benefit [3,6,7]. Likewise, the administration of ω-3 fatty acids in monotherapy form was ineffective.…”
Section: Results From Clinical Trialsmentioning
confidence: 99%
“…Arnold and colleagues (Arnold et al, 1989;Arnold, Kleykamp, Votolato, Gibson, & Horrocks, 1994) also expected supplementation with n-6 FA to demonstrate behavior improvement in ADHD children in whom a deficiency in Delta-6-desaturase was suspected. Arnold et al (1994) observed 18 boys with ADHD diagnosis in a double-blind placebo-controlled cross-over design. They compared n-6 FA supplementation (GLA: 320 mg, LA: 2,800 mg) with a drug (dextroamphetamine) and with a placebo.…”
Section: Referencementioning
confidence: 99%
“…70 Another study involving 18 boys with ADHD reported that use of 4000 mg evening primrose oil capsules produced little improvement in ADHD symptoms as compared to placebo. 71 The only factor in this study to signifi-…”
Section: Nutritional Factors In Autism and Adhdmentioning
confidence: 80%
“…71 Double-blind, placebo-controlled studies have reported that supplements of carnitine 72 and zinc 73,74 have been helpful in treating ADHD symptoms. Some studies have found that magnesium and vitamin B 6 supplements significantly reduce excitability and improve concentration in ADHD children.…”
Section: Nutrition Environment and Autism/adhdmentioning
confidence: 99%